2013
DOI: 10.1111/cdev.12176
|View full text |Cite
|
Sign up to set email alerts
|

Is Self‐Esteem a Cause or Consequence of Social Support? A 4‐Year Longitudinal Study

Abstract: Considerable research has been devoted to examining the relations between self-esteem and social support. However, the exact nature and direction of these relations are not well understood. Measures of self-esteem, and social support quantity and quality were administered to 961 adolescents across five yearly time points (M(age) = 13.41 years). Structural equation modeling (SEM) was utilized to test between a self-esteem antecedent model (self-esteem precedes changes in social support), self-esteem consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0
8

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(174 citation statements)
references
References 106 publications
14
135
0
8
Order By: Relevance
“…The present results clearly suggest that the selection effects of self-esteem on transitions in romantic relationships are adaptive, given that individuals with high self-esteem were more likely to begin a longer romantic relationship and less likely to experience relationship break-up. These findings correspond to evidence from other longitudinal studies, which suggested that self-esteem contributes to success and well-being in important life domains such as relationships, work, and health (Kuster et al, 2013;Marshall et al, 2014;Orth et al, 2012;Trzesniewski et al, 2006; for a review see Orth & Robins, 2014). The positive effects of selfesteem on the relationship domain are relevant given that romantic relationships are not only a potential source of well-being and life satisfaction, but frequently entail a number of other important consequences such as the possibility to start a family and the availability of social and material support (Dush & Amato, 2005;Sedikides, Oliver, & Campbell, 1994).…”
Section: Selection Effects Of Self-esteem On Relationship Transitionssupporting
confidence: 89%
“…The present results clearly suggest that the selection effects of self-esteem on transitions in romantic relationships are adaptive, given that individuals with high self-esteem were more likely to begin a longer romantic relationship and less likely to experience relationship break-up. These findings correspond to evidence from other longitudinal studies, which suggested that self-esteem contributes to success and well-being in important life domains such as relationships, work, and health (Kuster et al, 2013;Marshall et al, 2014;Orth et al, 2012;Trzesniewski et al, 2006; for a review see Orth & Robins, 2014). The positive effects of selfesteem on the relationship domain are relevant given that romantic relationships are not only a potential source of well-being and life satisfaction, but frequently entail a number of other important consequences such as the possibility to start a family and the availability of social and material support (Dush & Amato, 2005;Sedikides, Oliver, & Campbell, 1994).…”
Section: Selection Effects Of Self-esteem On Relationship Transitionssupporting
confidence: 89%
“…For example, longitudinal research suggests that people's self-esteem has consequences for the degree of success and well-being in important life domains such as romantic relationships and working life (Kuster, Orth, & Meier, 2013;Marshall, Parker, Ciarrochi, & Heaven, 2014;Orth, Robins, & Widaman, 2012;Trzesniewski et al, 2006). Future research should test whether these effects hold when the effects of narcissism are controlled for.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Thus, for example, Marshall et al (2014) showed that a system of reciprocal effects between self-concept and social support had attained equilibrium by junior high school.…”
Section: A Developmental Perspective: Developmental Invariance Hypothmentioning
confidence: 99%
“…The application of equilibrium and related terms has a long history in psychological theorizing more generally. Thus, for example, Marshall et al (2014) showed that a system of reciprocal effects between self-concept and social support had attained equilibrium by junior high school. We also note that support for such tests of developmental equilibrium facilitates the interpretation of the results, provides a more parsimonious model and results in statistically stronger tests of a priori predictions (also see Little et al, 2007).…”
Section: Section 4: Tests Of Developmental Invariance: Theoretical Bamentioning
confidence: 99%